Emergency Splenectomy for Blunt Splenic Rupture Complicated by Post-Traumatic Acute Kidney Injury and Multiple Organ Dysfunction Syndrome: A Case Report - Syifa Firza Aziza; Satrio Teguh Krisyuantoro; Pandu Anggoro; Dia Irawati; Fitria Nurul Hidayah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Multiple organ dysfunction syndrome is a leading cause of mortality after major blunt trauma. The spleen is the most frequently injured intra-abdominal solid organ, and when rupture occurs, it may precipitate haemorrhagic shock, systemic inflammatory response, and cascading failure of the kidneys, lungs, and coagulation system. Early recognition, rapid haemorrhage control, and coordinated multidisciplinary support are essential to limit progression and improve survival. Case presentation: A 30-year-old male motorcyclist presented to the emergency department after a high-velocity road traffic accident without helmet protection. On arrival, he was hypotensive (72/57 mmHg), tachycardic (140 bpm), apathetic with a Glasgow Coma Scale of 12, and had left upper quadrant tenderness with muscular defence. Focused assessment with sonography for trauma demonstrated free intraperitoneal fluid consistent with splenic rupture. Haemoglobin fell from 12.8 to 5.9 g/dL within hours and leukocytes rose to 37.8 ×10³/µL. An emergency splenectomy was performed for haemostasis. During the five-day intensive care course, he developed progressive oliguric acute kidney injury (peak creatinine 5.6 mg/dL, urea 114 mg/dL) requiring intermittent haemodialysis, hypercapnic respiratory failure (pH 6.969; pCO₂ 124.6 mmHg) requiring mechanical ventilation, stress hyperglycaemia (441 mg/dL) managed with insulin, and transient thrombocytopenia. Multidisciplinary care by trauma surgery, critical care, nephrology, and internal medicine resulted in haemodynamic stabilisation, recovery of renal function, and successful weaning from ventilation. Conclusion: Prompt haemorrhage control through emergency splenectomy, goal-directed resuscitation, early initiation of renal replacement therapy, metabolic support, and coordinated multidisciplinary intervention were decisive in mitigating trauma-induced multiple organ dysfunction syndrome in this patient and are proposed as pillars of management in similar presentations.